Solvatochromic fluorescent probes in bicontinuous microemulsions - Oliveira, M. E. C. D. R. (2001)
The fluorescence probes nile red and prodan have been used to study the structure of the bicontinuous phase of C12E5/alkane/water microemulsions. For nile red the steady state fluorescence spectrum show contributions from probe located in alkane and surfactant rich regions, together with indications of surfactant hydration. Fluorescence lifetime measurements show multiexponential decay kinetics consistent with this idea. The steady state fluorescence spectrum of prodan in the bicontinuous region also suggests different environments for the probe. Fluorescence anisotropy measurements using rhodamine 6G show that this bicontinuous phase is more ordered than either oil in water or water in oil microemulsions. The fluorescence technique provides a valuable tool with which to elucidate the structure of these complex systems.